6(2x-3)=-40

Simple and best practice solution for 6(2x-3)=-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-3)=-40 equation:


Simplifying
6(2x + -3) = -40

Reorder the terms:
6(-3 + 2x) = -40
(-3 * 6 + 2x * 6) = -40
(-18 + 12x) = -40

Solving
-18 + 12x = -40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 12x = -40 + 18

Combine like terms: -18 + 18 = 0
0 + 12x = -40 + 18
12x = -40 + 18

Combine like terms: -40 + 18 = -22
12x = -22

Divide each side by '12'.
x = -1.833333333

Simplifying
x = -1.833333333

See similar equations:

| 3x/3x-2-2/3x-2≠2/3 | | 8m-25=39mis | | 5+6t=10-7 | | 36x-96= | | 3x-4=5x-24 | | 1/3n-6=15 | | 30*365= | | 32x=16x^2 | | tan^2+4tan+2=0 | | 9-4n=7 | | 8m-25=30 | | 3x-4+10x-48=180 | | 3x-(x-(x-3))=-1 | | 3x-4+5x-12=180 | | (252)1/5 | | 8(t-4)+4t=4(3t+5)-10 | | 10(x-1)+4=12x | | 3*x-7=4*4+2 | | 8-2(t+5)=-2t-2 | | 3x/2-(x-1)/3=x/6 | | 6t+26=19t | | 3(y-7)=4(4+2) | | 8-2(t+5)= | | .2(x+3)-.5(x+3)=-.3x-.9 | | (5x-7)=(4x-6) | | 9x-2(2x+3)=x-4 | | -4(-9+x)=8 | | 2x-3(-2x+4)=13+x | | 2lnx=ln(10-3x) | | 3y+-8=y | | 5x^2-25=20x | | -3(6x+7)=-57 |

Equations solver categories